PERAN KOMUNIKASI MASSA PADA GUGUS TUGAS PERCEPATAN PENANGANAN COVID-19 PEMERINTAH KOTA AMBON - Marleen Muskita (BADATI, 2022)
Media has become an increasingly important human communication system in life. Mass communication has a crucial role in the midst of the Covid-19 pandemic which has been declared a global pandemic by the World Health Organization, namely WHO. As a result of Covid-19 coupled with the use of government mass communication which is less effective, the community becomes a dilemma, which causes people to choose between making a living with the risk of being exposed to Covid-19 or staying at home. In responding to this problem, the Ambon City Government works optimally in providing services to the community as well as using communication in providing information to the public. The purpose of the study, among others, is to determine the role of mass communication in the Ambon City government. This researcher uses a type of qualitative research, namely scientific research that seeks to find detailed data from cases. The results of this study prove that the role of mass communication today is indispensable. The communication carried out by the Ambon City Government task force was apparently carried out verbally and in writing. All of this is mainly related to efforts to invite the public to know and understand a certain problem, such as the current Covid-19 pandemic, which has turned out to be very effective. This is also evidenced by the public's acknowledgment that all information from the Ambon City government is very helpful for the community to understand the condition of the COVID-19 pandemic that is currently engulfing Ambon City and how to overcome and prevent it.